KAJIAN PENGARUH SEBELUM DAN SESUDAH PEMBANGUNAN JEMBATAN SURAMADU TERHADAP PENDAPATAN ASLI DAERAH DI KABUPATEN BANGKALAN - penangsang, parikesit; Studiviani, Pramita; Yuliaty, Hertien (JEB17 : Jurnal Ekonomi dan Bisnis, 2019)
Suramadu is a bridge that crosses the Madura Strait, with a length of 5,438 m, which connects Bangkalan Regency with the City of Surabaya and is the longest bridge in Indonesia today. Suramadu Bridge is believed to be able to increase the smooth flow of traffic or transportation of goods and people, which can stimulate economic development in Madura, especially in Bangkalan Regency. Economic development can be seen from the increasing economic growth through economic development in the real sector, namely in agriculture, industry, trade, services. Growth in the real sector will contribute to PAD in the form of taxes and levies, the influence of the two posts can be calculated using the Regression Analysis and Difference Test. 1) The results of the regression analysis are that before the suramadu bridge contributed fees to the PAD and the tax did not, but after the bridge the tax contributed to the PAD and the retribution did not. 2) Difference Test Results, before and after the Suramadu bridge, the tax post has a strong relationship and influence on PAD, because activities in the real sector are increasingly developing and increasing the flow of goods into the Regency. Bangkalan. However, the levies have less strong connection and less influence on PAD because the activities in Public Services, Business Services and Licensing are still underdeveloped (eg tourism, etc.). This economic situation needs the role and efforts of local governments to carry out economic development.